STUDENT SCIENCE AND TRAINING ENGINEERS - Shebashev, Viktor; Andrianov, Yuri; Nizova, Lyudmila; Nikitina, Anna (Journal of Applied Engineering Science, 2018)
The authors contemplate the forms of student science and their role in training engineers based on the documents of the International Labor Organization for Human Resources Management and Vocational Training: a case of technical universities in the Volga Federal District of the Russian Federation. The articles gives the dynamics of innovation-driven growth of Volga State University of Technology (Volgatech), students’ publication activity, students’ participation in the “UMNIK” programme and the number of incentives that the students were awarded at the Olympiads and competitions (with a breakdown by engineering professions). Based on monitoring, the authors defi ne the tendency of Volgatech graduates’ employment (with a breakdown by integrated groups of majors of engineering graduates).